Architectural Ruins and Urban Imaginaries: Carlos Garaicoa’s Images of Havana - Jodi Kovach (Contemporaneity: Historical Presence in Visual Culture, 2016)
Contemporary Cuban artist Carlos Garaicoa juxtaposes photographic images of Havana’s architectural ruins with timidly articulated drawings that trace the outlines of the dilapidated buildings in empty urbanscapes. Each of these fragile drawings, often composed of delicate threads adhered to a photograph of a site after demolition, serves as a vestige of the sagging structure that the artist photographed prior to destruction. The dialogue that emerges from these photograph/drawing diptychs implies the unmooring of the radical utopian underpinnings of revolutionary ideology that persisted in the policies of Cuba’s Período especial (Special Period) of the 1990s, and suggests a more complicated narrative of Cuba’s modernity, in which the ambiguous drawings—which could indicate construction plans or function as mnemonic images—represent empty promises of economic growth that must negotiate the real socio-economic crises of the present. This article proposes that Garaicoa’s critique of the goals and outcomes of the Special Period through Havana’s ruins suggests a new articulation of the baroque expression— one that calls to mind the anti-authoritative strategies of twentieth-century Neo-Baroque literature and criticism. The artist historically grounds the legacy of the Cuban Revolution’s modernizing project in the country’s real economic decline in the post-Soviet era, but he also takes this approach to representing cities beyond Cuba’s borders, thereby posing broader questions about the architectural symbolism of the 21st-century city in the ideological construction of modern globalizing society.